2005
DOI: 10.1164/rccm.200406-758oc
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived Neurotrophic Factor in Platelets and Airflow Limitation in Asthma

Abstract: Brain-derived neurotrophic factor (BDNF), a key mediator of neuronal plasticity, contributes to airway obstruction and hyperresponsiveness in a model of allergic asthma. BDNF is stored in human platelets and circulates in human plasma, but the significance of BDNF in this compartment is poorly understood. We investigated the relationship between platelet and plasma BDNF levels and pulmonary function in a cohort of 26 adult patients with recently diagnosed allergic asthma. BDNF levels in serum, platelets, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
100
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 36 publications
11
100
0
2
Order By: Relevance
“…Whether local oestradiol produced by granulosa cells within the ovary also alters extraneuronal neurotrophin expression remains to be determined. However, it has been shown that circulating levels of oestradiol are positively associated with BDNF concentrations in women undergoing fertility treatment (Monteleone et al 2007), and plasma BDNF levels fluctuate during a menstrual cycle (Cubeddu et al 2011), declining in post-menopausal women (Lommatzsch et al 2005, Pluchino et al 2009), but can be increased through hormone replacement . Steroid hormones also influence NGF.…”
Section: R49mentioning
confidence: 99%
“…Whether local oestradiol produced by granulosa cells within the ovary also alters extraneuronal neurotrophin expression remains to be determined. However, it has been shown that circulating levels of oestradiol are positively associated with BDNF concentrations in women undergoing fertility treatment (Monteleone et al 2007), and plasma BDNF levels fluctuate during a menstrual cycle (Cubeddu et al 2011), declining in post-menopausal women (Lommatzsch et al 2005, Pluchino et al 2009), but can be increased through hormone replacement . Steroid hormones also influence NGF.…”
Section: R49mentioning
confidence: 99%
“…It has also been shown that asthmatic patients demonstrate elevated levels of neurotrophins (NGF and BDNF) in serum and locally in the airways [3,4], and that allergen provocation significantly increases neurotrophin levels in the airways [2]. Increased neurotrophin (BDNF) concentration also correlated with clinical parameters of allergic airway dysfunction, such as airflow limitation and airway hyperresponsiveness, in asthmatic patients [5], whereas its level is normalised after treatment with inhaled corticosteroids [4]. However, to our knowledge, only one study has investigated neurotrophin (BDNF) levels in a paediatric population of asthmatic patients [6].…”
mentioning
confidence: 99%
“…A number of inflammatory cytokines and mediators, airway remodeling, neural reflexes, and secondary dysfunction of airway smooth muscle (ASM) all have been postulated to contribute to the development of AHR in patients with asthma. [2][3][4][5][6][7] Because of the vast array of inflammatory mediators present simultaneously in the asthmatic airway, the pathophysiological mechanisms responsible for AHR development have been exceedingly difficult to study in human beings.…”
mentioning
confidence: 99%